Pengaruh Genangan dan Pupuk Nitrogen terhadap Pertumbuhan dan Hasil Tanaman Kedelai - Rusmana Rusmana; Sri Ritawati; Eltis Panca Ningsih; Siska Kurnia (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Rusmana R, Sri Ritawati S, Ningsih EP, Kurnia S. 2020. The effect of waterlogging and nitrogen fertilizers on soybean plant growth and yield. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The purpose of this study is to find out the effect of waterlogging and treatment of different doses of N (Urea) fertilizer on the growth and yield of soybean crops (Glycine max L. Merr.). This type of research is experimental research conducted at Green House Faculty of Agriculture Sultan Ageng Tirtayasa Serang – Banten University in November to January 2020. This study used quantitative methods with Randomized Block Design (RBD) factorial, first factor waterlogging (G) consists of: g0 (100% Soil Water Available [SWA]), g1 (150% SWA), g2 (200% SWA), g3 (250% SWA) and the second factor of N fertilizer delivery namely n0 (0 kg/ha or without N), n1 (50 kg/ha), n2 (100 kg/ha) obtained 12 combinations of treatment each combination of repeated treatment 3 times until obtained 36 units of experiment. Each unit of experiment consists of 2 polybags so there are 72 polybags. The results showed that the treatment of waterlogging with 100% SWA had an effect on the number of filled pods per plant (13.00 pieces), the number of seeds per plant (27.67 grains), the wet weight of pods per plant (8.35 g), the dry weight of the pods per plant (1.76 g), and dry seed weight per plant (3.30 g). The treatment of fertilizer N shows no influence on the growth and yield of soybean crops. There is no interaction between waterlogging and N fertilizer in the growth and yield of soybean crops.